2020
DOI: 10.1136/bmjdrc-2019-000843
|View full text |Cite
|
Sign up to set email alerts
|

Impact of type 2 diabetes on postoperative outcome after hip fracture: nationwide population-based study in Taiwan

Abstract: SummaryThe impact of diabetes mellitus (DM) on hip fracture (HFx) is still controversial. We used nationwide population-based data in Taiwan to observe postoperative outcomes of HFx in patients with type 2 diabetes mellitus (T2DM) and found that the impact of T2DM may be related to medication of blood glucose control.ObjectivePublished studies evaluating diabetic patients with HFx have shown controversial outcomes. We assessed the impact of T2DM on postoperative outcomes after HFx in elderly patients using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…OP increases fracture risk and requires treatment to prevent subsequent comorbidities and mortality after fracture [ 19 , 22 , 25 , 26 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Knee OA leads to an increased risk of fall, which therefore increases fracture risk and required treatment [ 77 , 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…OP increases fracture risk and requires treatment to prevent subsequent comorbidities and mortality after fracture [ 19 , 22 , 25 , 26 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Knee OA leads to an increased risk of fall, which therefore increases fracture risk and required treatment [ 77 , 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review reported that 37.8% of Chinese diabetic subjects suffered from osteoporosis [ 3 ]. In addition, although the bone mineral density (BMD) in patients with type 2 diabetes mellitus (T2DM) is often normal or even elevated [ 4 ], diabetic individuals have an increased risk of fracture than those without T2DM [ 5 , 6 ]. In recent years, osteoporosis associated fracture has been considered an important complication of diabetes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In five studies, the number of patients undergoing surgical intervention was not clear [ 12 , 18 , 21 , 24 , 25 ]. All patients were treated surgically in eight studies [ 13 15 , 19 , 20 , 22 , 26 , 27 ] while in the remaining studies the number of patients treated surgically was > 78%. In one study [ 14 ] the follow-up was just 30 days.…”
Section: Resultsmentioning
confidence: 99%
“…These results concur with the generalized higher risk of mortality noted in men after hip fracture [ 33 , 34 ]. Considering the type of drug used for DM control, Behanova et al [ 12 ] and Lee et al [ 22 ] have noted significantly higher mortality in hip fracture patients on insulin as compared to those on oral hypoglycemic drugs. Contrastingly, Golinvaux et al [ 14 ] have noted no such difference in outcomes.…”
Section: Discussionmentioning
confidence: 99%